2016
DOI: 10.4238/gmr.15048375
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of sodium acetate on a human gastric adenocarcinoma epithelial cell line

Abstract: ABSTRACT. The objective of this study was to investigate the effect of sodium acetate on the viability of the human gastric adenocarcinoma (AGS) epithelial cell line. AGS cells were exposed to a range of concentrations of sodium acetate for different periods of time, and the sodium acetate-induced cytotoxic effects, including cell viability, DNA fragmentation, apoptotic gene expression, and caspase activity, were assessed. The changes in these phenotypes were quantified by performing a lactate dehydrogenase ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
(28 reference statements)
2
7
0
Order By: Relevance
“…This is in accord with literature reports, because cytotoxic effects of sodium acetate and acetate ions on human cells have been extensively studied [77,78,79,80]. For example, it has been reported that acetate ions induce cell death and apoptosis either in colorectal carcinoma cells [77] or human gastric adenocarcinoma cell lines [78]. It has also been determined that the cytotoxicity of acetate can be induced through coupling with cellular proteins via molecular mechanisms [79] and acetate can promote the release of reactive oxygen species [80].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in accord with literature reports, because cytotoxic effects of sodium acetate and acetate ions on human cells have been extensively studied [77,78,79,80]. For example, it has been reported that acetate ions induce cell death and apoptosis either in colorectal carcinoma cells [77] or human gastric adenocarcinoma cell lines [78]. It has also been determined that the cytotoxicity of acetate can be induced through coupling with cellular proteins via molecular mechanisms [79] and acetate can promote the release of reactive oxygen species [80].…”
Section: Resultssupporting
confidence: 91%
“…This suggests that the cytotoxicity of CdSe(S)/ZnO QDs is not related to cadmium, because the shell of zinc oxide protects the core against oxidation, but there are some un-reacted acetate ions in the aqueous solution of CdSe(S)/ZnO QDs that restrict cell viability. This is in accord with literature reports, because cytotoxic effects of sodium acetate and acetate ions on human cells have been extensively studied [77,78,79,80]. For example, it has been reported that acetate ions induce cell death and apoptosis either in colorectal carcinoma cells [77] or human gastric adenocarcinoma cell lines [78].…”
Section: Resultssupporting
confidence: 89%
“…Due to its role in stress-response signaling and regulation, acetate might be expected to have anti-cancer effects in addition to pro-cancerous effects, depending on the cell type of origin and the tumor microenvironment. For example, acetate has been shown to have anti-cancer effects in colon cancer, adrenocarcinoma, and glioma cell lines, although the molecular mechanisms underlying these effects remain poorly understood (Long et al, 2013b(Long et al, , 2015Marques et al, 2013;Xia et al, 2016). High concentrations of acetate have also been shown to be cytotoxic to thymic tumor cells in vitro, whereas the same concentration of acetate (12.5 mM) was not toxic to normal thymocytes (Pandey et al, 2018a).…”
Section: Acetate In Cancermentioning
confidence: 99%
“…lysosomal and mitochondrial permeabilization (Marques et al, 2013). Also, acetate is known to induce apoptosis in some cancer cells in a caspase-dependent manner (Xia et al, 2016). In many cases, the cell-specific effects may be through acetatebased epigenetic mechanisms, regulating gene transcription.…”
Section: Acetate In Cancermentioning
confidence: 99%
“…LDH increased in Lactobacillus sakei cells [NRIC 1071(T)] cultivated with 50 mM SA, and L. sakei strains shifted from the dl ‐type to the l ‐type at this concentration . The release of reactive oxygen species by acetate could be an underlying mechanism of SA cytogenotoxic effect …”
Section: Discussionmentioning
confidence: 99%